Mobile phone SIM card: A security concern in the perspective of Bangladesh - Hasan, Nazmul; Ahmed, Mohammad Riasat; Islam, Raisul; Majadi, Nazia (16th Int'l Conf. Computer and Information Technology, 2014)
At present time the unregistered SIM cards (here unregistered means the SIM cards which are registered with false information provided by dealer) are widely used for committing crimes in the perspective of Bangladesh. Due to the complexity of the present SIM card registration process, the subscribers are reluctant to register themselves. In this paper we propose a cloud based system model which demonstrates an online method of SIM card purchasing and registration. This system model conquers the constraints of the conventional system of mobile purchasing and registration which is lengthy and stalking. It enables the subscriber to buy the SIM card and to be registered in an uncomplicated way. Here we mainly emphasize on the security issue through mandatory mobile SIM card registration. The purpose of our system model is lessening the rate of crimes which can be taken place by the use of mobile. We also show that how this system will encourage the people to be a registered user and at the same time discourage the criminals to commit crime with the use of mobile call and SMS.